Occurrence of Lymphatic Filariasis infection after 15 years of mass drug administration in two hotspot districts in the Upper East Region of Ghana. - Derrick Adu Mensah; Linda Batsa Debrah; Peter Akosah Gyamfi; Abu Abudu Rahamani; Vera Serwaa Opoku; John Boateng; Prince Obeng; Jubin Osei-Mensah; Inge Kroidl; Ute Klarmann-Schulz; Achim Hoerauf; Alexander Yaw Debrah (PLoS Neglected Tropical Diseases, 2022)
Background Lymphatic filariasis (LF) causes chronic morbidity, which usually manifests as lymphedema or hydrocele. Mass drug administration (MDA) began in Kassena Nankana East Municipal (KNEM) and Nabdam, two hotspot districts in the Upper East Region in Ghana, in 2000 and 2005, respectively. This cross-sectional study evaluated the impact of 15 years of MDA on the control of LF as determined by circulating filarial antigen (CFA) and microfilariae assessment in the KNEM and the Nabdam districts. Methodology/principal findings A total of 7,453 participants from eight sub-districts in the two hotspot districts (KNEM: N = 4604; Nabdam: N = 2849) were recruited into the study. The overall CFA prevalence as determined by the FTS was 19.6% and 12.8% in the KNEM and Nabdam districts, respectively. Manyoro, a sub-district on the border with Burkina Faso, recorded the highest CFA prevalence of 26% in the KNEM. Assessment of microfilariae and Og4C3 antigen was done from 1009 (KNEM: N = 799 (79.2%); Nabdam: N = 210 (20.8%)) randomly selected FTS-positive (N = 885) and FTS-negative (N = 124) individuals. The Og4C3 antigen was found in 22.6%/23.0% of the selected individuals (KNEM/Nabdam), whereas the night blood revealed microfilariae in only 0.7%/0.5%. Conclusions/significance Using the WHO endorsed FTS, CFA prevalence exceeded the long-standing <2% threshold-which may need revision and validation. Surprisingly, the Og4C3 ELISA showed positive results in only about one-fifth of the FTS positive samples. However, even this result would not have met the <2% CFA criteria for LF elimination. In contrast, projections from the microfilariae results revealed a halt in LF transmission. The global elimination target was due in 2020 but has been extended to 2030 since this could not be met. Focused MDA intervention intensification on seasonal migrants and non-compliers, and implementation of alternative treatment strategies may suffice for the elimination of the disease.